2017
DOI: 10.4103/jpbs.jpbs_88_17
|View full text |Cite
|
Sign up to set email alerts
|

Maternal risk factors and periodontal disease: A cross-sectional study among postpartum mothers in Tamil Nadu

Abstract: Background and Aim:It is inconclusive that periodontitis is an independent risk factor for adverse pregnancy outcomes. This study aims to investigate the association between maternal periodontitis and preterm and/or low birth weight babies.Settings and Design:This was a prospective cross-sectional study. After prior informed consent, 3500 postpartum mothers were selected from various hospitals in Tamil Nadu and categorized into the following groups: group-1 – Normal term normal birth weight (n = 1100); Group-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
1
8
1
Order By: Relevance
“…In Jordan, another study reported a slightly higher prevalence (31%) of periodontal disease was documented in pregnant women [29]. In India, Govindasamy et al recently reported that over half (54.8%) of postpartum women had periodontal diseases [30], which was nears to our results. In Mali, West Africa, another study was carried out among 74 pregnant women reported; 49% of cases diagnosed with periodontitis [31].…”
Section: Discussionsupporting
confidence: 84%
“…In Jordan, another study reported a slightly higher prevalence (31%) of periodontal disease was documented in pregnant women [29]. In India, Govindasamy et al recently reported that over half (54.8%) of postpartum women had periodontal diseases [30], which was nears to our results. In Mali, West Africa, another study was carried out among 74 pregnant women reported; 49% of cases diagnosed with periodontitis [31].…”
Section: Discussionsupporting
confidence: 84%
“…This finding was found to be higher than the studies conducted in Sudan, 24.0%, 17 in Tanzania, 14.2%, 14 in Brazil, 17.24%, 83 and in Jordan, 31%. 15 In contrast to this, this study was found to be lower as compared with the studies conducted in Amsterdam, 67%, 84 in India, 54.8%, 13 and in China, 84.7%. 85 This discrepancy might be due to different populations, study designs, variation in sample size, and the use of different tools that may contribute to the differences observed.…”
Section: Discussioncontrasting
confidence: 60%
“…The prevalence of the periodontal disease is varied across different settings and populations, for instance, the reported prevalence of PD in the United States (US), 10 Latin America, 11 and India 12 was 50%, 40–80%, and 96.3%, respectively. The prevalence of periodontitis among pregnant women is also varied across different parts of the world 13–15 such as 11% in Brazil, 10 60.5% in Rwanda, 16 24.0% in Sudan, 17 and 42.4% in Northwest Ethiopia. 18 …”
Section: Introductionmentioning
confidence: 99%
“…A slightly higher prevalence (31%) of periodontal disease was documented in pregnant women in Jordan [13]. Interestingly, Govindasamy et al recently reported that over half (54.8%) of postpartum women in India had periodontal diseases [11]. Moreover, much higher rates (84.7% and 73.9%) of periodontal disease were reported among women of childbearing age (preconception) in China [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of periodontal disease among pregnant women varies in different populations [11][12][13]. Moreover, several factors such as age, parity, lower level of education and anaemia were identified as risk factors for periodontal disease during pregnancy [4,14].…”
Section: Introductionmentioning
confidence: 99%